In vitro assessment of the factors that determine the activity of the rumen microbiota for further applications as inoculum. (16th July 2018) - Belanche, Alejandro; Palma‐Hidalgo, Juan M; Nejjam, Ibtissam; Serrano, Rosa; Jiménez, Elisabeth; Martín‐García, Ignacio; Yáñez‐Ruiz, David R
Abstract: BACKGROUND: The rumen microbiota has been used as inoculum for in vitro studies and as a probiotic to improve productivity in young animals. However, great variability across studies has been noted depending on the inoculum considered. The present study aims to assess the relevance of different factors (microbial fraction, collection time, donor animal diet, fermentation substrate and inoculum preservation method) to maximize the rumen inoculum activity and set the standards for further in vitro and in vivo applications. RESULTS: Rumen inoculum sampled at 3 h after feeding led to greater microbial growth and activity [+12% volatile fatty acid (VFA), +17% ammonia] compared to before feeding. Similar results were noted when rumen liquid or rumen content were used as inocula. Rumen inoculum adapted to concentrate diets increased microbial activity (+19% VFA) independently of the substrate used in vitro . Freezing‐thawing the inoculum, in comparison to fresh inoculum, decreased microbial activity (−14% VFA, −96% ammonia), anaerobic fungi and protozoa, with holotrichs protozoa being particularly vulnerable. Inoculum lyophilization had a stronger negative effect on microbial activity (−51% VFA) and delayed re‐activation of the microbes, leading to lower levels of methanogens and anaerobic fungi, as well as almost complete wipe out of rumen protozoa. CONCLUSIONS: Fresh rumen fluid sampled at 3 h after feeding from donor animals that were fed concentrate diets should be chosen when the aim is to provide the most diverse and active rumen microbial inoculum. © 2018 Society of Chemical Industry